Rehabilitation interventions - Turk, Margaret A.; Mudrick, Nancy R. (SAGE Publications, Inc., 2013)
Explores issues involving rehabilitation interventions and therapies and examines topics central to the lives of individuals with disabilities and their families.
Keywords: People with disabilities -- Rehabilitation.; Medical rehabilitation.; People with disabilities -- Medical care.; Healing.; People with disabilities -- Services for.; People with disabilities -- Functional assessment.; Rehabilitation.; Rehabilitation; Persons with Disabilities -- rehabilitation.; Recovery of Function; Personnes handicapées -- Intégration.; Personnes handicapées -- Services.; Personnes handicapées -- Évaluation fonctionnelle.; Réadaptation.; Personnes handicapées -- Services de santé.; Guérison.; pardons.; MEDICAL -- Physical Medicine & Rehabilitation.; People with disabilities -- Services for; People with disabilities -- Functional assessment; Healing; Medical rehabilitation; People with disabilities -- Medical care; People with disabilities -- Rehabilitation